Residual stress measurements on SS316L specimen using selective laser melting and numerical computation software / Micheal Stoschka ... [et al.] - Stoschka, Micheal; -, Liyana Balqis; Fladischer, Stefan; Taufek, Thoufeili; HP Manurung, Yupiter; Adenan, Mohd Shahriman; Krishnamoorthy, Renga Rao (Smart Manufacturing Research Institute (SMRI), 2023)
This research aimed to predict the residual stress of additively manufactured rectangular specimen using Selective Laser Melting (SLM) by means of non-linear numerical computation based on Thermo-mechanical method (TMM). The procedure started with the geometrical and material modelling of rectangular specimen with regard to Austenitic Stainless Steel 316L (SS316L) in which the temperature dependent material data properties such as Young’s Modulus, Thermal Expansion Coefficient, Specific Heat Capacity and Thermal Conductivity were considered. The next phase consisted of numerical computation procedure in which the specimen was positioned 60° of inclination angle from the substrate plate. The support structure was to be generated within the lower surface of the specimen in order to avoid the material from collapsing during printing process. Laser heat source was modelled based on the laser beam width, power, efficiency and scanning speed in order for the numerical computation to accurately predict the thermal problem of SLM process. Furthermore, layer parameters used to fabricate the specimen such as hatch distance, hatch scan width and layer thickness were taken into TMM consideration. Similar set-up from numerical computation by means of laser and layer parameters to fabricate SS316L rectangular specimen was utilized in real fabrication process using SLM machine, Renishaw RenAM 500E. After fabrication of the specimen, electropolishing as for the sample preparation of X-Ray Diffraction (XRD) measurement was conducted by means of various depths on both sides of the specimen. For the validation procedure, residual stress on every depth was analysed and compared with the result from numerical computation. In conclusion, TMM simulation forecasted an acceptable residual stress of SLM product with relative error up to 14% and the computational time taken to predict the residual stress was only 56 minutes. This exploratory research using TMM simulation to predict residual stress of SLM product could benefit metal additive manufacturing (MAM) production as a whole by neglecting expensive trial and error approach.